Model of the "department" ecosystem - Kryvyi, S.L.; Grinenko, O.O. (Інститут програмних систем НАН України, 2024)
An ecosystem model is proposed, which describes the main objects and their functions in such medium of a higher educational institution as a department. The main object of research in such models are conditions of the successful development and functioning of the department. In particular, the methods of planning an equal educational load for teachers, together with the employees of the university department and the management of the faculty are considered. The main actors in the ecosystem are teachers (called servers), who teach the courses. The proposed model makes it possible to simplify the drawing up of the schedule, to quickly respond to force majeure circumstances, necessary exchange of the teacher, etc. The properties of ecosystem models are verified by automata-network methods. Such ecosystem can be generalized and expanded by adding models of the faculty, university, and Ministry in order to control the work of the faculty, university, and ministry, the effectiveness of their functioning.Prombles in programming 2024; 2-3: 418-425